A Dual‐Mode Colorimetric/Fluorescent Sensor Comprising Rhodamine B and Piperazine: Response to Acidic pH Values and Investigation of Recognition Mechanism. Issue 11 (17th March 2020) - Wu, Fang‐hui; Luo, Xiang‐rui; Yang, Jun‐qing; Ren, Mei‐juan; Wei, Xian‐wen; Yan, Zhengquan
Abstract: A dual‐mode "turn‐on" fluorescent‐colorimetric sensor, 1‐methyl piperazine rhodamine amide (MPRA ), has been identified and developed for acidic pH detection in practice. After its structure and photophysical property were characterized and investigated in detail, it was noted to find that nonfluorescent and colorless MPRA would present rose Bengal color and emit strong saffron yellow fluorescence simultaneously with pH decreasing from 7.2 to 1.8 in PBS/acetonitrile (1 : 1, v/v). Under the optimized conditions, MPRA expressed an excellent partitioned and dual‐mode response to pH, i. e ., ranging from 1.8 to 3.6 and 3.6 to 7.2 for fluorescent analysis, and 1.8 to 4.0 and 4.0 to 7.2 for colorimetric one with the acidity constant ( K a ) of 1.75 obtained from Henderson‐Hasselbach equation. Importantly, the sensing was real‐time and reversible, which was successfully applied for pH detection in real fruit aqueous samples with R.S.D. less than 5.0%. The selective recognition mechanism for MPRA to H + was confirmed to be the ring‐opened amide form mechanism by 1 H NMR and theoretical calculation. MPRA will be a potential dual‐mode sensor for on‐site monitoring pH in acidic environments. Abstract : A novel rhodamine B derivative containing piperazine moiety (MPRA) was developed. It was a visible sensor for dual‐mode "turn‐on" fluorescent‐colorimetric detection of acidic pH. The sensor was successfully applied for pH detection in real fruit samples with excellent results. The recognition mechanism was the ring‐opened amide owing to the chelating of H + to MPRA with p Ka of 1.75.